Investment opportunities for venture capitalists - an analysis based on people ventures - Dalgas, Frederik (2022)
This paper aims to present a methodology for how Venture Capitalists analyze and select new market opportunities for investments, examining People Ventures as a case study. The methodology’s development is based upon past literature, forward-looking trends, and completed transactions supported by quantitative analysis. The result of the analysis is an investment thesis. Ultimately, the Chronic Care and Connected Retail sub-verticals have been selected as the key market segments to invest in, as they have a good strategic fit to People Ventures, attractive markets and exit environments, and upward trending deal patterns to suggest continued growth in the spaces.